INSTANT SOUP MIX FORTIFIED WITH BROCCOLI AND CABBAGE POWDER: A FUNCTIONAL FOOD APPROACH - S, Suvetha; L, Venipriyadharshini (International Journal of Pharma and Bio Sciences, 2025)
The study focused on the development and evaluation of an instant soup mix powder formulated with broccoli and cabbage powders, aimed at enhancing nutritional value, sensory appeal, and shelf stability. Five variations incorporating different proportions of broccoli and cabbage were prepared and subjected to organoleptic analysis using a 9-point hedonic scale. Among them, Variation III was identified as the most acceptable in terms of appearance, flavour, texture, colour, taste, and overall acceptability. Physicochemical evaluations revealed improved functional properties in the test sample, with higher oil (2.6 ml/g) and water absorption capacities (5.2 ml/g) compared to the control. Nutritional analysis showed significantly higher energy (379 kcal), carbohydrate (68.1 g), and protein (19.4 g) contents in the test sample. Microbiological analysis confirmed product safety, with minimal bacterial presence even after 15 days of storage. Cost analysis indicated the developed soup mix (₹101/112g) to be cost-effective compared to commercial alternatives. The findings suggest that the broccoli and cabbage-based instant soup mix powder is a promising, nutritious, and economical product suitable for commercial production and public consumption. Its high acceptability and improved nutritional profile position it as a potential functional food in the growing market for healthy convenience foods.